2019
DOI: 10.1186/s42055-019-0012-y
|View full text |Cite
|
Sign up to set email alerts
|

Participation in planning and governance: closing the gap between satisfaction and expectation

Abstract: Background: Making and implementing decisions to improve long term sustainability, particularly in democratic countries, is a significant challenge. This is exacerbated when citizens' expectations of their relationship with government is significantly at odds with what they experience, since this is likely to further reduce their already low trust in government and its decision-making. Research in the USA has demonstrated a clear gap between citizens' expectations of their participation in government and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 50 publications
4
26
0
Order By: Relevance
“…Instead, they experience "consultation" or "informing," several levels lower on the ladder. This performance/expectation gap was detected in government officials as well as the general public in case studies in the US and Australia [55]. These results overlap with other authors who have found sometimes contradictory preferences for participation in surveys that force dichotomous choices on participants between pure citizen or pure technocratic government control [50,[60][61][62].…”
Section: Public Participation As a Way Of Building Political Trustsupporting
confidence: 65%
See 3 more Smart Citations
“…Instead, they experience "consultation" or "informing," several levels lower on the ladder. This performance/expectation gap was detected in government officials as well as the general public in case studies in the US and Australia [55]. These results overlap with other authors who have found sometimes contradictory preferences for participation in surveys that force dichotomous choices on participants between pure citizen or pure technocratic government control [50,[60][61][62].…”
Section: Public Participation As a Way Of Building Political Trustsupporting
confidence: 65%
“…Thus, given the link between participation and trust in government, it is important to ask: What type of participation do citizens expect, and are governments living up to this expectation? Recent research in Australia and the US [55,56] using the tool of a modified Arnstein ladder [55,57,58] (see Figure 1) found a difference between the level of participation that citizens would ideally like and that which is being provided to them-known as the Arnstein gap [59].…”
Section: Public Participation As a Way Of Building Political Trustmentioning
confidence: 99%
See 2 more Smart Citations
“…First, as noted previously, shared responsibility and authority are highly desirable in efforts to resolve wicked problems. Second, survey research from the USA [78] and Australia [79] has shown that citizens prefer a "partnership" relationship with their government rather than an increase in empowerment. They want neither complete control nor marginal consultation, but rather a decision-making process that is respectful of the strengths, resources and experience of ordinary people in combination with the experience and knowledge of elites, and the learning that goes with both.…”
Section: Commit To and Prepare For Localised Sdg Deliberative Democramentioning
confidence: 99%